Large Animal Models of Cell-Free Cardiac Regeneration - Spannbauer, Andreas (Biomolecules, 2020)
The adult mammalian heart lacks the ability to sufficiently regenerate itself, leading to the progressive deterioration of function and heart failure after ischemic injuries such as myocardial infarction. Thus far, cell-based therapies have delivered unsatisfactory results, prompting the search for cell-free alternatives that can induce the heart to repair itself through cardiomyocyte proliferation, angiogenesis, and advantageous remodeling. Large animal models are an invaluable step toward translating basic research into clinical applications. In this review, we give an overview of the state-of-the-art in cell-free cardiac regeneration therapies that have been tested in large animal models, mainly pigs. Cell-free cardiac regeneration therapies involve stem cell secretome- and extracellular vesicles (including exosomes)-induced cardiac repair, RNA-based therapies, mainly regarding microRNAs, but also modified mRNA (modRNA) as well as other molecules including growth factors and extracellular matrix components. Various methods for the delivery of regenerative substances are used, including adenoviral vectors (AAVs), microencapsulation, and microparticles. Physical stimulation methods and direct cardiac reprogramming approaches are also discussed.